Preparation, structural elucidation and biocidal applications of trimethyltin(IV) complexes derived from substituted carboxylic acids. Issue 10 (October 2020) - Mehmood, Mehwish; Din, Imtiaz-ud; Raheel, Ahmad; Haq, Ihsan-ul; Tahir, Muhammad Nawaz
Abstract: A series of trimethyltin(IV) carboxylates (1-7), having general formula [(CH3 )3 SnOOCR], where R = 3-CF3 C6 H4 - (1), 3, 4-(OCH2 CH3 )2 C6 H3 - (2), 3-FC6 H4 - (3), 4-ClC6 H5 - (4), 2, 4-(OCH3 )2 C6 H3 - (5), 4-NO2 C6 H4 - (6), 5-CH3 C4 H2 N2 - (7) have been synthesized and are characterized by using analytical techniques like, FT-IR, 1 H, 13 C and 119 Sn NMR spectroscopy in addition to elemental analyses. To validate the structural motif, one of the complex (2) was also analyzed by single crystal XRD technique. The single crystal X-ray diffraction analysis revealed that the molecular species exist in one dimensional polymeric chain, wherein five coordinated tin is attached to two oxygens of the carboxyl and three carbon atoms of CH3 groups, whereas the bond angles for C-Sn-C (117.20–121.65°), C-Sn-O (87.87–98.60°) and O-Sn-O (173.75°) lie in the predictable range of distorted trigonal bipyramidal geometry. All the synthesized complexes were also subjected to preliminary screening for various biocidal applications such as antimicrobial, anti-diabetic, protein kinase inhibition and brine shrimp lethality test to check their efficacy. The compound 6 exhibits very good antibacterial activity having MIC value 6.25 μg/mL against K. pneumoniae, whereas antidiabetic and protein kinase inhibition data revealed that 1 and 2 may serve as good to moderately effective inhibitors, respectively. Abstract : Organic Chemistry, Trimethyltin(IV), Carboxylates, X-ray structure, Tau, Enzyme Inhibition, Antimicrobial.